Relation between age at first alcohol drink & adult life drinking patterns in alcohol-dependent patients - Soundararajan, Soundarya (Indian J Med Res, 2017)
BACKGROUND & OBJECTIVES: Age at first drink has its influence on later life drinking patterns. The association between age at first drink and adult alcohol consumption has not been studied in clinical population. This study was aimed to determine the age at first drink and its correlation with adult life drinking patterns in alcohol-dependent patients. METHODS: Adult participants with alcohol dependence were included from the inpatient and outpatient wards of a tertiary care de-addiction facility in India. Questionnaires administered were National Institute on Alcohol Abuse and Alcoholism-Quantity Frequency for alcohol and the Fagerstrom Test for Nicotine Dependence for tobacco. RESULTS: Of the 99 participants (92% males) with mean age 37±8.36 yr, mean age at first drink was 21.14±5.33 yr. After controlling for age, satisfaction with life scores and smoking, age at first drink showed a significant negative correlation with drinking days per week (r=-0.259, P=0.012), typical drink per day (r=-0.218, P=0.035) and maximum drinks in the previous month/year (r=-0.233, -0.223 and P=0.024, 0.031, respectively). INTERPRETATION & CONCLUSIONS: Our study suggested that earlier age of first drink correlated with chronic heavy drinking patterns in later adult life in alcohol-dependent patients. This may have implications for alcohol control policies determining the age for legal consumption.